Optimal postoperative refraction for good unaided near and distance vision with monofocal intraocular lenses. - Bradbury, J A (1992)
Forty five eyes with up to 2 dioptres of myopic astigmatism and up to 1 dioptre sphere either plus or minus following cataract extraction and implantation of a monofocal intraocular lens were examined to assess their unaided visual acuities. Forty three percent were able to see 6/12 and N8, and 60% were able to see 6/12 and N10. Subjects with between 1 and 2 dioptres of myopic astigmatism and virtually no sphere were able to see 6/12 and N10 in 82% of cases. This study confirms the benefits to both distance and near vision of myopic astigmatism as an alternative to multifocal intraocular lenses.